RETRACTED: Do Chinese children need parental supervision to manage their out-of-school visual art activities and academic work time? - Endale Tadesse; Sabika Khalid; Chunhai Gao; Moges Assefa Legese (Frontiers in Psychology)
Unlike in Western countries, scholars and the Chinese government pay less attention to the role of extracurricular activities (ECAs) in fostering children’s cognitive and non-cognitive well-being. Accordingly, essential ECAs such as visual arts programs are serviced by expensive privately owned schools, creating social injustice. The primary aim of the current study is to examine whether children benefit from ECAs if parental support and guidance for managing time spent on ECAs and academics exist based on the threshold model. The study comprised over 2,400 primary school students in one Chinese province and considered the SES of the area. Surprisingly, the present study’s findings illustrate that contemporary Chinese parents differ from traditionally aggressive and overbearing parents who do not value their children’s interests. However, the current study finding suggested that children’s participation in out-of-school visual art activities doesn’t have a substantial value in promoting children’s academic performance in the face of genuine interest and supportive parenting, which negates the threshold model.